Tahap Development dalam Metode ADDIE Pengembangan Bahan Ajar berbasis Mobile - Rangga Bayu Rinawan; Zaenal Mustofa; Yussi Anggraini (Jurnal Publikasi Teknik Informatika, 2024)
Teaching materials are sources of knowledge that are useful as sources of information used by teachers and students in teaching and learning activities. Printed teaching materials are currently expensive and difficult to obtain. Current technological developments support the development of modern teaching materials and can be accessed anytime and anywhere. Mobile-based teaching materials are a solution to this problem. Through this product, teachers can provide complete material accompanied by a guide to conducting practicums. Teachers can monitor students' learning progress from the application and provide guidance if there are questions from students. Students can use the product with direct guidance from the teacher. So that the learning process will be well directed. This article discusses the development stage of the ADDIE method (Analyze, Design, Development, Implementation and Evaluation). The analyze and design stage has been published in another article. This development stage discusses the initial formation of the product to become a product. The product being developed can be seen starting from the initial login display, the main menu containing the features available in the application, the material menu containing various materials and function buttons inside along with the quiz menu with buttons that are useful as supporting quizzes.